Servicio al cliente en la lubricadora y lavadora Black Door de La Ciudad de Babahoyo. - Medina Flores, Byron Rodrigo (2022)
The present case study was developed with the objective of knowing the factors that affect customer satisfaction in the Black Door lubricator and washing machine in the city of Babahoyo, for which the qualitative methodology was used, which aims to describe and analyze the culture and behavior of human beings and their groups from the perspective of the researcher. The type of descriptive research was also used, which allows the characteristics of a population or phenomenon to be analyzed without knowing the relationships between them. For the present work, a survey technique was applied that allowed collecting primary information from the customers of the Black Door lubricator and washing machine through a structured questionnaire that was developed for this purpose. This case study is related to the research subline of the trade career "Marketing and commercialization", the administrators of the premises had all the predisposition to provide the necessary information, as well as the active participation of the clients when answering the respective questionnaire.